Avaliação dos dados climáticos históricos no estado da Paraíba e seu uso em estudos de energia fotovoltaica - Silva, Louise Pereira da (2021)
Climate change can have consequences on the performance of units generating electricity from renewable resources, as these technologies are dependent on the climate of the region of installation. From historical series of climatic data and statistical applications, such as the Mann-Kendall test quantified by the slope of Sen, it is possible to investigate evidence of climate change. The state of Paraíba, which is located in the Northeast region of Brazil, was selected as the study area in the present study. The climatic behavior of meteorological stations data from the National Institute of Meteorology (INMET) and estimated climatic data were studied, in addition to the influence on the productivity of monocrystalline and polycrystalline silicon photovoltaic systems. The presence of significant decreasing trends was verified through the Mann-Kendall test, quantified by the slope of Sen, in the INMET total horizontal solar irradiation data, at Areia and Cabaceiras stations, which means that there was a reduction in solar irradiation. In the dispersion analyzes (MAE and RMSE) of the total horizontal solar irradiation data, between INMET and the National Aeronautics and Space Administration (NASA), three NASA stations presented an acceptable error in relation to the INMET data. The calculated diffuse horizontal radiation from INMET, related to data from the Reference Center for Solar and Wind Energy Sérgio de Salvo Brito (ABES) and NASA, showed little variation over the year. The average air temperature showed significant upward trends in the annual period in all seasons. The Spearman correlation between the total horizontal solar radiation and the cell operating temperature was significant for all models of photovoltaic panels. The impact on photovoltaic production based on the increase in average air temperature was less than 1% for all seasons. Even though the variation in photovoltaic production has been small so far, there are indications that this impact will increase in the future. Thus, it is necessary to be aware of climate change and how it can affect energy sectors. For this, more research must be carried out on the subject, in order to obtain more in-depth knowledge and elaborate possible alternatives to mitigate these impacts of climate change.